(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the multifaceted role of metaphor within literary texts, emphasizing its function not only as a linguistic device for conveying information and aesthetic expression but also as a crucial source of cultural knowledge. The study examines the structural, cognitive, and interpretive aspects of metaphor. It highlights metaphor’s capacity to articulate complex emotional states, construct poetic worldviews, and shape narrative progression through extended and recurring figurations. The discussion further addresses the cognitive mechanisms underlying metaphor comprehension, focusing on culturally embedded receptive schemas that facilitate the decoding of implicit meaning. The article underscores metaphor’s irreplaceability by literal paraphrase, noting its unique ability to encapsulate aestheticized emotion and individual authorial vision.